Basal Autophagy Is Altered in Lagotto Romagnolo Dogs with an ATG4D Mutation. (November 2017) - Syrjä, Pernilla; Anwar, Tahira; Jokinen, Tarja; Kyöstilä, Kaisa; Jäderlund, Karin Hultin; Cozzi, Francesca; Rohdin, Cecilia; Hahn, Kerstin; Wohlsein, Peter; Baumgärtner, Wolfgang; Henke, Diana; Oevermann, Anna; et al.
A missense variant in the autophagy-related ATG4D -gene has been associated with a progressive degenerative neurological disease in Lagotto Romagnolo (LR) dogs. In addition to neural lesions, affected dogs show an extraneural histopathological phenotype characterized by severe cytoplasmic vacuolization, a finding not previously linked with disturbed autophagy in animals. Here we aimed at testing the hypothesis that autophagy is altered in the affected dogs, at reporting the histopathology of extraneural tissues and at excluding lysosomal storage diseases. Basal and starvation-induced autophagy were monitored by Western blotting and immunofluorescence of microtubule associated protein 1A/B light chain3 (LC3) in fibroblasts from 2 affected dogs. The extraneural findings of 9 euthanized LRs and skin biopsies from 4 living affected LRs were examined by light microscopy, electron microscopy, and immunohistochemistry (IHC), using antibodies against autophagosomal membranes (LC3), autophagic cargo (p62), and lysosomal membranes (LAMP2). Biochemical screening of urine and fibroblasts of 2 affected dogs was performed. Under basal conditions, the affected fibroblasts contained significantly more LC3-II and LC3-positive vesicles than did the controls. Morphologically, several cells, including serous secretory epithelium, endothelial cells, pericytes, plasma cells, and macrophages, contained cytoplasmic vacuoles with an ultrastructure resembling enlarged amphisomes, endosomes, or multivesicular bodies. IHC showed strong membranous LAMP2 positivity only in sweat glands. The results show that basal but not induced autophagy is altered in affected fibroblasts. The ultrastructure of affected cells is compatible with altered autophagic and endo-lysosomal vesicular traffic. The findings in this spontaneous disease provide insight into possible tissue-specific roles of basal autophagy.